Counselling and Psychotherapy: Professionalisation in the Australian Context - Denis O’Hara; E. Fiona O'Hara (Psychotherapy and Counselling Journal of Australia)
Counsellors and psychotherapists contribute significantly to the mental health and well-being of communities around the world but have struggled to establish professional recognition more so than other mental health professionals. While the struggle for professional status has varied greatly in different jurisdictions, the Australian experience has been particularly challenging. This paper provides a rationale for recognising counselling and psychotherapy as a profession and identifies the key remaining structural hindrances to this outcome. In particular, the introduction of the Medicare Better Access Initiative and the approach taken to credentialing, among other factors, are identified as influential constraints on the profession. These issues are discussed and recommendations for moving the profession beyond these limitations are proposed.